2007
DOI: 10.1245/s10434-007-9412-x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Reverse Mapping (ARM): A New Concept to Identify and Enhance Lymphatic Preservation

Abstract: ARM identified significant lymphatic variations draining the upper extremities and facilitated preservation in all but one case. ARM added to present-day ALND and SLNB further defines the axilla and may be useful to prevent lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
217
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(233 citation statements)
references
References 31 publications
9
217
1
1
Order By: Relevance
“…Rate of Identification of arm lymphatics varies from 33.3% in initial studies to as high as 91% with use of radio isotopes, [8,9]. In our study, using methylene blue dye injection, at the start of surgery, blue lymphatics were identified in72.2 % while blue lymph nodes could be identified in 61.1%.The pattern of distribution of arm lymphatics in axilla varies with respect to axillary vein .…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Rate of Identification of arm lymphatics varies from 33.3% in initial studies to as high as 91% with use of radio isotopes, [8,9]. In our study, using methylene blue dye injection, at the start of surgery, blue lymphatics were identified in72.2 % while blue lymph nodes could be identified in 61.1%.The pattern of distribution of arm lymphatics in axilla varies with respect to axillary vein .…”
Section: Discussionmentioning
confidence: 47%
“…A number of techniques have been described in literature for the identification of arm lymphatics in the axilla, using blue dye [4,6,8], radio isotope [9] and fluorescence [17]. Rate of Identification of arm lymphatics varies from 33.3% in initial studies to as high as 91% with use of radio isotopes, [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) (Boneti et al, 2008;Casabona et al, 2008Casabona et al, , 2009Nos et al, 2007;Ponzone et al, 2008;Thompson et al, 2007). Thompson et al (2007) injected 2.5 mL of blue dye intradermally or subdermally into the upper inner arm along the medial intramuscular groove of the ipsilateral arm. After injection, the site was massaged and the arm elevated for 5 min to enhance arm lymphatic drainage.…”
Section: Mapping By Blue Dye Injectionmentioning
confidence: 99%
“…Several cooperative group trials have shown lymphedema rates in range of approximately 7% with sentinel lymph node biopsy alone (Sakorafas et al, 2006;Wilke et al, 2006). Recently, the axillary reverse mapping technique has been developed to map and preserve arm lymphatic drainage during axillary lymph node dissection and/or sentinel lymph node biopsy (Nos et al, 2007;Thompson et al, 2007). This technique is based on the hypothesis that the lymphatic pathway from the arm cannot be involved by metastasis of the primary breast cancer.…”
Section: Introductionmentioning
confidence: 99%